Pengaruh Inflasi, BI7DRR, Nilai Tukar, ROA, dan DER Terhadap Return Saham Pada Perusahaan Indeks LQ45 di Bursa Efek Indonesia Periode 2017-2021 - Petrus Pirhot Silalahi (Universitas Batanghari, 2022)
The existence of the capital market in Indonesia is one of the most important factors in the effort to participate in building the national economy. One of the most popular investments in the capital market is stocks. Stock is one of the attractive financial instrument investments because it can provide high returns but is also high risk. This study aims to analyze the effect of macroeconomics consisting of inflation, BI7DRR, exchange rates, and company fundamentals as proxied by ROA and DER ratios on company stock returns in the LQ45 stock index listed on the Indonesia Stock Exchange. The population in this study amounted to 69 companies that have joined the LQ45 stock index during the 2017-2021 period. The sampling technique used is purposive sampling by setting certain criteria. The samples obtained were 27 companies. The data analysis technique used is descriptive statistical analysis and panel data regression with the help of the Eviews version 9.0 program as a data processing tool to present statistical information. The results of the model specification test show the random effect model as the best model in estimating panel data regression. The results showed that inflation and exchange rates had a negative and significant effect on stock returns. BI7DRR has a positive and significant effect on stock returns. Meanwhile, ROA and DER have no significant effect on stock returns. Simultaneously inflation, exchange rate, BI7DRR, ROA and DER have a positive and significant effect on stock returns. This finding illustrates that LQ45 stock returns are more dominantly influenced by macroeconomic factors than company fundamentals. This can be used as consideration for investors in determining an effective investment strategy.